An enzyme-activatable dual-readout probe for sensitive β-galactosidase sensing and Escherichia coli analysis - Huang, Yifang; Feng, Weiwei; Zhang, Guo-Qiang; Qiu, Yuling; Li, Linlin; Pan, Liqiu; Cao, Nannan (Frontiers in Bioengineering and Biotechnology, 2022)
Rapid and accurate sensing of β-galactosidase (β-gal) activity is particularly critical for the early detection of many diseases and has become a topic of interest in recent years. However, most traditional probes for β-gal sensing often suffered from the disadvantages of narrow dynamic range, low reaction efficiency and are only employed with either colorimetric or fluorescence sensing. Furthermore, β-galactosidase sensing based assay for efficient detection and antibiotic resistance analysis of Escherichia coli (E.coli) is not available. Here, an enzyme-induced probe assay was reported for dual sensitive fluorescence and colorimetric measurement of β-gal activity, and was further employed for detection of Escherichia coli and their antibiotic resistance analysis. The DCM-βgal probe was virtually non-emissive in aqueous solution, while it could be activated by β-gal to produce bright emission. Under optimized conditions, DCM-βgal displayed high sensitivity, selectivity and rapid response to β-gal with a low detection limit of 1.5 × 10−3 U•mL-1. Importantly, this assay was successfully applied to sensitive detection of E. coli cells with a fast detection process within 5 hours and a low detection concentration of 1×103 CFU•mL−1. Furthermore, the enzyme-activatable assay was also successfully applied for high throughput E. coli antibiotic resistance analysis. The DCM-βgal strategy is applied for the first time on the detection of E. coli cells and their antibiotic resistance analysis. It is provided with the advantages of high selectively, a simple operation, low cost and rapid detection. The detection platform can also be extended to analyze the level of β-gal in other types of cells or biological samples. Overall, the simple, effective and dual-readout assay holds promise for efficient sensing of β-gal activity and provides a potential tool for E. coli detection and their antibiotic resistance analysis.